Evaluation of Strawberry Colletotrichum spp. Genetic Diversity in Lithuania - Armina Morkeliūnė; Neringa Rasiukevičiūtė; Birutė Frercks; Vidmantas Bendokas; Raminta Antanynienė; Ingrida Mažeikienė; Viktorija Vaštakaitė-Kairienė; Rasa Karklelienė; Alma Valiuškaitė (Agronomy)
Strawberry anthracnose is becoming more important from a scientific and economic standpoint. The Colletotrichum spp. pathogen complex includes C. fragariae, C. gloeosporioides and C. acutatum. The aim was to use microsatellite (SSR) markers to assess the genetic diversity of Colletotrichum species. We used seven SSR primer pairs previously developed for the C. acutatum (3) and C. gloeosporioides (4) species. To analyze the genetic diversity of C. fragariae, it was discovered that SSR primer pairs created for C. gloeosporioides were helpful. SSR molecular markers were used in this study for the first time to identify the species of C. fragariae. The average polymorphism information content (PIC) value across all SSR primer pairs was 0.72, making them all informative. The most informative SSR primers were CG22 and CG30, with PIC values of 0.83 and 0.82, respectively. We believe these primers are suitable for the genetic diversity analysis of C. fragariae species. Therefore, the SSR primer pairs CG20 and CG30 are suggested for the genetic investigation of C. acutatum and C. gloeosporioides. A higher incidence of Colletotrichum spp. polymorphism in Lithuania can be linked to adaptation to survival in our environment, according to this study’s findings on the number of alleles and the degree of genetic diversity, which are higher than the results reported in the literature.